Usefulness of non-invasive cardiac output monitoring in elderly patients undergoing monopolar transurethral resection of the prostate: a pilot study. Issue 5 (May 2020) - Kil, Hae Keum; Park, In Kyeong; Song, Min Sup; Park, Jin Ha
Objective: To assess the impact of irrigating fluid on hemodynamic profiles using real-time non-invasive cardiac output monitoring (NICOM) in elderly patients undergoing monopolar transurethral resection of the prostate (TURP). Methods: Twenty patients between 65 and 80 years of age who were scheduled for monopolar TURP and received spinal anesthesia up to T10 were enrolled. Irrigating fluid (2.7% sorbitol with 0.5% mannitol solution) was used. Hemodynamic profiles including cardiac index, and stroke volume variation (SVV) using NICOM were obtained. Estimated irrigating fluid absorption was indirectly calculated. Results: The median amount of irrigating fluid used was 6000 mL. The median SVV was 11%, which increased to 12% at 10 minutes after initiating surgery. No significant changes in the cardiac index were observed. The estimated absorption of irrigating fluid was almost zero. Conclusions: Although the estimated amount of irrigating fluid that was absorbed was negligible, the increase in SVV may indicate intravascular volume depletion with diuresis resulting from mannitol in the irrigating fluid early during irrigation. Therefore, even during short irrigating times, intensive hemodynamic monitoring should be performed to monitor the possibility of intravascular volume depletion as well as volume overload, especially immediately after large amounts of irrigating fluid are used.